Human inhibitory leukocyte Ig-like receptors: from immunotolerance to immunotherapy - Calvin D. De Louche; Ali Roghanian (JCI Insight, 2022)
In recent decades, immunotherapeutic strategies have been used to treat a wide range of pathologies, many of which were previously incurable, such as cancer and autoimmune disorders. Despite this unprecedented success, a considerable number of patients fail to respond to currently approved immunotherapies or develop resistance over time. Therefore, there is an urgent need to develop the next generation of immune-targeted therapies. Various members of the Ig superfamily play essential roles in regulating leukocyte functions. One such group, the leukocyte Ig-like receptors (LILRs), have been implicated in both innate and adaptive immune regulation. Human inhibitory LILRs (LILRBs) are primarily expressed on leukocytes and mediate their signaling through multiple cytoplasmic immunoreceptor tyrosine-based inhibitory motifs. Engagement of LILRBs by endogenous and pathogenic ligands can markedly suppress immune responses, leading to tolerance or immunoevasion, whereas blocking these inhibitory receptors can potentiate immune responses. In this Review, we discuss the immunoregulatory functions of human LILRBs and the potential of targeting them to manipulate immune responses in various pathologies.